ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA PEKALONGAN (Students' Journal of Accounting and Banking, 2013)
Receipts Revenue (PAD) is a significant source of revenue for financing development in a routine and autonomous regions. The amount of local tax revenue components and levies greatly influenced by many types of local taxes and levies are applied and adapted to the regulations relating to the acceptance of these two components. This study analyzes the contribution of local taxes and levies with data analysis techniques such as multiple linear regression and a sample of census techniques. The data sample used local tax revenue, levies and Pekalongan city revenue in fiscal year 2009-2012.Contribution of local tax revenue and levies to the acquisition of Pekalongan City Government PAD using sampling techniques such as census data over a period of Fiscal Year 2009-2012. In the 2009-2010 budget year significant tax revenue to the average local tax contribution of 30.17 percent per year. While the average contribution of 27.35 percent levy. In order to enhance the ability of local governments to implement regional autonomy, the central government set the Law No. 28 Year 2009 on Regional Taxes and Levies. The result in the year 2011 and 2012 revenue increased PAD in Pekalongan 33.37 and 43.98 percent from a year earlier. Contribution to the Local Tax revenue also increased to reach 31.43 in 2011 and 33.55 percent in 2012.To further enhance the contribution of local tax revenue and levies to total revenue receipts and revenue as well as enlarge Pekalongan city government needs to be done collecting the types of local taxes and levies in accordance with Law No. 28 of 2009 to establish the basic rules of Regulation levied.Keywords: source revenue, local taxes and levies. Keywords : Local own revenues, local taxation, and local retribution